Relationship between fuzzy edge connectivity and the variables in clinical waste incineration process - Baharun, Sabariah; Ahmad, Tahir; Mohd. Yusof, Mohd. Rashid (Faculty of Science, 2009)
Structured networks of interacting components are hallmarks of several complex systems and clinical waste incineration process is an example of such a system. Fuzzy graph theory provides important tools to capture various aspects of complexity, imprecision and fuzziness of the network structure of the incineration system as compared to the discrete description of relation of its crisp graph. This paper discusses he use of fuzzy edge connectivity in describing the relation between the variables in he incineration process. It begins with the definition of fuzzy graph that involves fve different types of graph fuzziness in which fuzzy edge connectivity constitutes its hird type. The fuzzy edge connectivity and the membership values of the fuzzy edge onnectivity based on the chemical reactions of the variables of the system are defined and illustrated respectively. Fuzzy graph showing the relation between the variables are also depicted in a diagram to give a better picture of the relation between these variables